Curriculum Vitae_ Deputy Vice Chancellor - Research, Innovation & Outreach,Professor of Medical Microbiology and infectious diseases - Jaramogi Oginga Odinga University of Science and Technology - Prof. Estambale, Benson B. (JOOUST, 2018)
Position: Deputy Vice Chancellor (Research,Innovation and Outreach)